SNP Marker Discovery in Pima Cotton (Gossypium barbadense L.) Leaf Transcriptomes - Kottapalli, Pratibha (Genomics Insights, 2016)
The objective of this study was to explore the known narrow genetic diversity and discover single-nucleotide polymorphic (SNP) markers for marker-assisted breeding within Pima cotton (Gossypium barbadense L.) leaf transcriptomes. cDNA from 25-day plants of three diverse cotton genotypes [Pima S6 (PS6), Pima S7 (PS7), and Pima 3-79 (P3-79)] was sequenced on Illumina sequencing platform. A total of 28.9 million reads (average read length of 138 bp) were generated by sequencing cDNA libraries of these three genotypes. The de novo assembly of reads generated transcriptome sets of 26,369 contigs for PS6, 25,870 contigs for PS7, and 24,796 contigs for P3-79. A Pima leaf reference transcriptome was generated consisting of 42,695 contigs. More than 10,000 single-nucleotide polymorphisms (SNPs) were identified between the genotypes, with 100% SNP frequency and a minimum of eight sequencing reads. The most prevalent SNP substitutions were C—T and A—G in these cotton genotypes. The putative SNPs identified can be utilized for characterizing genetic diversity, genotyping, and eventually in Pima cotton breeding through marker-assisted selection.